The importance of rim removal in deep lateral orbital wall decompression - Kakizaki H (Dove Medical Press, 2011)
Hirohiko Kakizaki1, Yasuhiro Takahashi1, Akihiro Ichinose2, Masayoshi Iwaki1, Dinesh Selva3, Igal Leibovitch41Department of Ophthalmology, Aichi Medical University, Nagakute, Aichi, Japan; 2Department of Plastic Surgery, Kobe University, Kobe, Hyogo, Japan; 3South Australian Institute of Ophthalmology and Discipline of Ophthalmology and Visual Sciences, University of Adelaide, South Australia, Australia; 4Division of Oculoplastic and Orbital Surgery, Department of Ophthalmology, Tel Aviv Medical Center, Tel Aviv University, Tel Aviv, IsraelPurpose: To evaluate the surgical outcome of deep lateral orbital decompression with or without rim removal.Design: Retrospective case series.Methods: Thirty-two patients (47 orbits) with Graves’ orbitopathy who underwent simple deep lateral decompression or balanced lateral plus medial decompression. Of the 14 patients (24 orbits) who underwent simple deep lateral decompression, 8 (13 orbits) had temporary rim removal and in 6 (11 orbits) the rim was left intact. Of the 18 patients (23 orbits) who underwent a balanced decompression, 7 (9 orbits) had temporary rim removal and in 11 (14 orbits) the rim was left intact. The amount of postoperative reduction in proptosis was compared among these four groups.Results: The average reduction in proptosis in the simple deep lateral decompression group was 5.73 mm (range: 4.0–8.0 mm) in the rim removal group and 4.09 mm (range: 2.5–6.0 mm) in the intact rim group (P = 0.005). The average reduction in proptosis in the balanced decompression group was 6.39 mm (range: 5.0–8.5 mm) in the rim removal group and 5.07 mm (range: 3.0–8.0 mm) in the intact rim group (P = 0.039). There was no statistically significant difference in proptosis reduction between the simple deep lateral decompression with rim removal group and the balanced decompression with an intact rim group (P = 0.220).Conclusion: The rim removal approach allows a more effective decompression than the intact rim approach. Simple deep lateral decompression with rim removal approach has a similar effect to balanced decompression through an intact rim.Keywords: deep lateral decompression, balanced decompression, rim removal, intact rim, Graves’ orbitopathy, proptosis